Influence of color centers on the luminescent response of radiation-damaged CsI:Tl crystal - Yakovlev, V.; Trefilova, L.; Alekseev, V.; Karnaukhova, A.; Shpylynska, O.; Lebedynskiy, A.; Tarakhno, O. (Functional Materials, 2018)
Luminescence properties of Tl⁰va⁺ and Tl⁺vc⁻ color centers induced by irradiation in CsI:Tl crystal are studied within a temperature range of 80-300 K. It is found, that electron Tl⁰va⁺ and hole Tl⁺vc⁻ color centers arising due to radiation damage do not reduce conversion efficiency of CsI:Tl crystal, but participate in scintillation process to get energy from Tl⁺ centers by resonance. Degradation of the light yield of the irradiated CsI:Tl crystal is caused by the radiative energy transfer from Tl⁺ to Tl⁰va⁺ centers, whose emission is quenched at temperature above 210 K. Non-radiative energy transfer from Tl⁺ to Tl⁺vc⁻ centers results in long-wave spectral shift and the duration increase of the scintillation pulse.